Impact of Digital Empowerment on University Performance: Evidence from Northern Border University in Saudi Arabia - Ibrahim, Ahmed Ibrahim Hassan (European Journal of Sustainable Development, 2024)
The COVID-19 pandemic, known as Covid-19, has caused unprecedented disruption in global education systems, impacting approximately 1.6 billion students across over 190 countries and affecting universities and other educational institutions profoundly. In response to this crisis, educational institutions have increasingly turned to technological advancements and the implementation of distance learning and e-learning platforms as viable alternatives to traditional educational methods. This shift has necessitated faculty members to assume new roles, managing educational processes through virtual classrooms, taking part in remote collaboration in interdisciplinary teams and making decisions pertaining to distance education. The implementation of digital empowerment in educational settings is contingent upon these endeavors. The purpose of this research is to evaluate the effect of digital empowerment on institutional performance at universities. In order to do this, 320 people, or 23% of the study population, responded to a questionnaire that was issued to 1,358 faculty members in order to test a number of hypotheses. Multiple regression analysis results show that 40.2% of the variance in institutional performance may be explained by digital empowerment and the five sub-variables it was explored in this study. This emphasizes how important digital empowerment is for improving university operations, especially at Northern Border University. Keywords: Remote learning, digital learning platforms, and academic institutions